Designing and fabricating mini lathe machine for low volume production - Nik Azman Abadi, Nik Daniel Haziq; Mohd Yusof, Ab Aziz; Ismail, Ainaa Maya Munira (Universiti Teknologi MARA Cawangan Johor Kampus Pasir Gudang, 2025)
This research focuses on developing a compact and cost-effective mini lathe machine capable of producing small and precise components. The bench lathe was chosen for its versatility, ease of use, and suitability for woodworking applications. The design process involved using SolidWorks for modelling, and Finite Element Analysis (FEA) was conducted to assess structural integrity. 1345 Aluminium Alloy was selected for its strength-to-weight ratio and durability. The analysis revealed that the spindle experienced a maximum stress of 7.6 MPa, well below its yield strength of 27.57 MPa, with a Factor of Safety (FoS) of 3.4, ensuring safe operation. The prototype successfully performed cutting, grinding, and turning with minimal difficulties. While it is limited to wood due to motor constraints, it meets all design and fabrication objectives. Regular maintenance is required for long-term functionality. Overall, the mini lathe machine demonstrates efficiency, reliability, and practicality for small scale applications.